Weaving Invisible Threads: The Impact of Caregiver Trauma on Parenting and Child Brain Development - Manessa Riser; Christopher Trentacosta; Tanja Jovanovic (Brain Sciences)
Trauma exposure has severe consequences for the exposed individuals as well as their children. The current paper is a conceptual narrative review that uses the intergenerational transmission of trauma (ITT) framework to synthesize the literature on the association between a parent’s exposure to trauma and the brain and behavioral outcomes in their children. There are likely multiple mechanisms for the ways in which parental history of trauma exposure can lead to these negative outcomes. However, this review highlights parenting as a key pathway through which caregiver trauma conveys both the risk and resilience in the child’s neurodevelopment, emphasizing the need for trauma-informed, relationship-focused interventions.